Buildings classification using applied technology council (ATC – 21) - Ramli, Mohd. Zamri (Penerbit UTM, 2008)
Every earthquake provides new lessons for the earthquake engineering profession. Most naturally occurring earthquakes are related to the tectonic natu re of the earth. Such earthquakes are called tectonic earthquakes. Earthquake is a shake in earth crus t that causes of a sudden high energy that release from the ear th. This energy maybe causes of a tectonic force in the earth crust. The earth crust is made from a cold and fragile rock and it is different from the layer under it where it is hotter than earth crust. The crack earth crust will wreck and form to piece of rock. This piece of rock will collide each other and ca use a pressure that produce a shake and known as earthquake. This shake will produce a seismic wave that can be transforming to kinetic force and next will cause damage to structure when it can’t absorb or control this kinetic energy. The method to absorb and control the kinetic force before it damage the structure is equipped the structure with seismic isolator. This paper describes the ATC – 21. The method wh ereby buildings can be rapidly identified via a “sidewalk survey from the exterior” as seis mically acceptable or potentially seismically hazardous. In generally, a Structural Score which cons ists of a series of “s cores” and “modifiers” based on building attributes that can be seen from the street. The Structural Score S is related to the probability of the building sustaining life-threaten ing damage should a severe earthquake in the region occur. A low “S” score suggests th at the building requires additional study by a professional engineer experienced in seismic desi gn (further investigatio n) and a high “S” score indicates that the building is pr obably adequate. Finally, a location map of Putrajaya Precint 1 is developed to show all buildings weat her its need ATC – 21 or ATC – 22